Analisis Faktor-faktor yang Mempengaruhi Minat Beli Asuransi Syariah dengan Brand Image sebagai Variabel Intervening - Annisa Anindya; Rijal Arslan; Kristiurman Jaya Mendrofa (Indonesian Journal of Islamic Economics and Business, 2025)
This study aims to assess the impact of Price, Product Suitability, and Service Quality of Sharia General Insurance on Purchase Intention, with Brand Image serving as an intervening variable. A quantitative approach is used in this research, employing accidental sampling, with 125 respondents from the Greater Jakarta area (Jabodetabek) who are already familiar with Sharia General Insurance. The data analysis method applied is path analysis. The results of hypothesis testing, as part of the inner model evaluation, show that the Price and Product Suitability variables do not significantly influence Purchase Intention, either directly or indirectly. In contrast, the Service Quality variable significantly affects Purchase Intention through Brand Image as an intervening variable. Service Quality also significantly influences Brand Image. The Brand Image variable, acting as an intervening variable in this study, is shown to have a significant impact on Purchase Intention. To enhance public interest in Sharia General Insurance in Jabodetabek, companies should focus on strengthening their Brand Image to improve recognition and trust among potential customers. Additionally, service quality should be enhanced by incorporating distinct Sharia characteristics, such as utilizing the Sharia ecosystem to provide added value for consumers.